Biosynthesis of Lacto-N-fucopentaose I in Escherichia coli by metabolic pathway rational design. (1st December 2022) - Hu, Miaomiao; Li, Mengli; Li, Chenchen; Zhang, Tao
Abstract: Lacto- N -fucopentaose I (LNFP I), a member of the fucosylated human milk oligosaccharides (HMOs) family, has received widespread attention because of its importance in infant health. However, constructing a low-cost microbial cell factory for high-efficient production of complex fucosylated HMOs remains challenging. Herein, an efficient engineered strain for LNFP I biosynthesis was reported by metabolic pathway rational design in Escherichia coli BL21(DE3). The fed-batch cultivation of engineered strains produced 2.11 g/L LNFP I, and the conversion rate of lacto- N -tetraose (LNT) to LNFP I reached 32.55 %, the highest level reported so far. The LNFP I-produced platform established here is broadly suitable for complex and branched HMOs production. Graphical abstract: Unlabelled Image Highlights: The de novo biosynthesis of LNFP I was achieved by engineering Escherichia coli . Efficient production of LNFP I was achieved by metabolic reprogramming. A promising strategy for complex and branched HMOs production was provided.